The Forming of Moral Qualities of Future Teacher by Means of Parables - Nelina Khamska (Pedagogical Discourse, 2016)
The article highlights the parables’ educational potential, it clarifies and expands the scientific understanding of the parables’ role in the moral consciousness formation, moral feelings and adolescent students’ behavior formation, the examples that prove the effectiveness of the parables usage in the future teachers’ professional prepararion are given.The methodology of the parables usage for the moral qualities of the future teacher’s formation in the process of pedagogical disciplines’ studying is also highlighted. The concept of symbolic and context studying as an effective method of the future teacher’s moral qualities formation by means of parables is grounded. The stages of the future teacher’s moral qualities formation by means of parables are characterized (on the level of information exchange); valuable attitude to others formation (on the dialogue basis); the usage of the acquired moral experience in the future teacher’s professional occupation (in the process of pedagogical practice), that guaranteed the stability of moral believes, understandings and aims. The author explains the peculiarities of parables usage in the educational process: the participants’ preparation for the parable perception; parable’s narration; parable’s discussion – problem setting, key episodes analyses, the system of questions and answers building, comparative analyses leading and summarizing of some images and plots, motivation and logical explanation of the revealed differences, conclusions’ formation.The article summarizes the idea that parables’ usage in the educational and upbringing process ensures future teacher’s valuable life guidelines formation and his valuable attitude to other people; it activates the interest to the process of moral experience gaining and striving for sharing it with other people; it develops the ways of moral behaviour mastery. Key words: ethics, moral education, the parable, the parable as a means of educational influence, parables’ educational potential.